1971
DOI: 10.1677/joe.0.0500187
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Determining the Distribution and Source of Protein in Preovulatory Rat Ovaries

Abstract: SUMMARY The distribution and source of protein in the fluid compartments of tissues may be determined by the use of [14C]sucrose to determine the volume of the fluid compartments and 125I-labelled serum albumin ([125I]SA) to determine the distribution volume of the labelled protein. The amount of tissue protein in the ovary, the amount of protein derived from plasma, the rate of plasma protein influx into the ovary and the amount of newly synthesized protein were calculated. Immature female rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent reports have implicated adrenergic receptors in the follicle wall in ovulation (Kannisto et al, 1985;Wylie et al, 1985 ;Spicer, 1986). Also, beta-adrenergic receptors in ovarian blood vessels, when stimulated, increase blood flow, resulting in an increase in antral fluid volume (Lipner and Smith, 1971;Espey, 1980;Kannisto et al, 1985). This increase may cause a transient rise in intrafollicular pressure, resulting in a distension-induced contraction of the follicular wall.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have implicated adrenergic receptors in the follicle wall in ovulation (Kannisto et al, 1985;Wylie et al, 1985 ;Spicer, 1986). Also, beta-adrenergic receptors in ovarian blood vessels, when stimulated, increase blood flow, resulting in an increase in antral fluid volume (Lipner and Smith, 1971;Espey, 1980;Kannisto et al, 1985). This increase may cause a transient rise in intrafollicular pressure, resulting in a distension-induced contraction of the follicular wall.…”
Section: Discussionmentioning
confidence: 99%
“…Since the smooth musculature in the walls of the ovarian blood vessels is also influenced by ß-agonists (Varga, Zsolnai & Bernard, 1979), the flow through the ovarian tissue should be increased in the presence of terbutaline due to vasodilatation. It has been shown that the intrafolli¬ cular pressure is influenced by the ovarian blood flow (Lipner & Smith, 1971), and the net effect of a ß-receptor stimulation might thus be an increased intrafollicular pressure. This could be another factor promoting an increased incidence of ovulations.…”
Section: Discussionmentioning
confidence: 99%